The Correlation Between Air Pollution Exposure Duration and Occurence of Emphysema Based on Chest CT Scan in Public Transportation Drivers - Yopi Simargi; Jessica Seprianto; Bryany Titi Santi (Jurnal Respirologi Indonesia, 2021)
Background: Emphysema is included in chronic obstructive pulmonary disease (COPD) whose prevalence tends to increase in Indonesia. Air pollution is one of risk factor for emphysema. Public transportation drivers are one of the most vulnerable occupation exposed to air pollution. This study aimed to determine the correlation between air pollution exposure duration and occurence of emphysema in public transportation drivers. Methods: This was an analytic observational study using a cross-sectional approach. Samples of this study (n=32) were public transportation drivers in North Jakarta. Data were collected during August – October 2019 at Atma Jaya Hospital, North Jakarta. The study datawere secondary data obtained through interviews and chest CT scan. Data analysis was performed using Fisher’s exact method. Results: The prevalence of emphysema was 46,9% with 9 respondents (60%) had mixed type emphysema and 13 respondents (87,7%) had mild degrees. The prevalence of public transportation drivers exposed to air pollution for more than or equal to 8 hours a day was 87,5%. There was a significant correlation between air pollution exposure duration and occurence of emphysema (P=0,038). Conclusion: There was a statistically significant correlation between air pollution exposure duration and occurence of emphysema. As many as 11 respondents (39,3%) exposed to air pollution for more than or equal to 8 hours a day exposure were found to have emphysema. However, all respondents in this study were smokers, which was also a risk factor for emphysema and could be considered as severe air pollution.